Isolation, Cloning and Expression of Recombinant Human Renin in Escherichia Coli System - Ng, Chyan Leong (2002)
Renin is an important honnone in kidney regulating the renin-angiotensin system (RAS); which plays an important role in human blood pressure. Renin is a highly specific endopeptidase cleaving the Leu-Leu bond in angiotensinogen to generate angiotensin I. Recently, renin was found in organs other than the kidney such as adrenal, ovary, testis, uterus, placenta, anterior pituitary and brain, implicating its involvement in the regulation of numerous activities. Prorenin is the inactive precursor of the renin which regulates the blood pressure and electrolyte balance. Prorenin can be activated in vitro following nonproteolysis and proteolysis. The isolation of prorenin or renin from organs including kidney is extremely difficult due to its very low concentration and its instability. Therefore, recombinant protein technologies are used to produce the recombinant human renin protein. In this study, the full-length human renin coding gene (REN) was isolated from the human kidney cDNA library by using the polymerase chain reaction (PCR) technique. The primers (RF1 & RR1) used were designed based on the human mRNA renin gene sequence from GenBank [gi |4506474| ref | NM_000537.1|]. The PCR amplified REN gene was cloned into pCR-Blunt cloning vector. Sequencing was carried out and the result shows 99.9% identical to the published sequence. The REN gene was cloned into two different E. coli expression vectors, pRSETB and pGEX4T l , to express the recombinant protein. Construct pRB-R was successfully expressed in E. coli strains BL2 1-S1 and BL21 (DE3)pLysS with the recombinant protein corresponding to the expected size -48 kDa. Construct pGT-R was expressed in BL2 1 (DE3)pLysS with the size -66 kDa. Both recombinant proteins have been confirmed with western blotting by using monoclonal anti-His antibody (recombinant protein derived from pRSET vector) and monoclonal anti-GST antibody (recombinant protein derived from p GEX4Tl vector). The result of the expression shows that the combination of the expression vector pRSETB and host BL2 1 (DE3)pLysS gave the highest soluble fraction of recombinant protein.